Decentralization in the Democratic Republic of Congo : Opportunities and Risks - World Bank; European Commission (World Bank, Washington, DC, 2014)
The aim of this summary note is to highlight the technical complexity of the decentralization process in the Democratic Republic of Congo (DRC) as well as the risks and opportunities inherent in it. It also provides a review of the in-depth work conducted on the fiscal aspects of the decentralization process, which is crucial to obtain an understanding of the real life impact of the "40 percent" rule and the difficulties inherent in its practical application. It also provides an overview of potential solutions to the dilemmas faces by Democratic Republic of Congo's (DRC's) policy makers. In this regard, this note will review four key aspects of the decentralization process (fiscal aspects and competency transfers, human resource issues and capacity development, legal supervision issues, public investment management and the equalization fund) as well as a transversal analysis of the impact of these four aspects of the process on the education sector. This note, which is the result of joint work by experts from the World Bank and the European commission, considers technical aspects of the various elements of the decentralization debate.